Human Resource Management Strategy in Improving Employee Performance at PT Kino Indonesia Tbk - Riesha, Riezky Army (International Journal of Management Science and Information Technology, 2026)
Employee performance remains a central determinant of organizational competitiveness within the fast-moving consumer goods (FMCG) industry, particularly for companies such as PT Kino Indonesia Tbk operating amid intensifying market competition and accelerating human resource digitalization. This article aims to describe and analyze, through the lens of the Ability-Motivation-Opportunity (AMO) framework, the human resource management strategies disclosed by PT Kino Indonesia Tbk and to examine how these strategies collectively relate to employee performance improvement. This study employs a qualitative descriptive research design through library research, drawing secondary data from the company’s 2022 and 2023 Annual Reports and 2024 Sustainability Report, analyzed using a structured thematic analysis procedure. The findings indicate that PT Kino Indonesia Tbk implements three interrelated strategies corresponding respectively to the ability, opportunity, and motivation dimensions: tiered competency-based development, evidenced by an increase in training hours per employee from 4.57 in 2022 to 9.18 in 2023; a digital learning platform enabling self-directed employee development; and welfare-oriented sustainability practices under the Thriving People pillar, reflected in full health-insurance coverage and complete maternity-leave reinstatement, alongside an 11 percent turnover rate in 2024. These findings demonstrate that the three strategies function as a mutually reinforcing system rather than isolated initiatives, contributing theoretically to sustainable human resource management literature by illustrating the applicability of the AMO framework to publicly disclosed corporate HR strategy, while offering practical implications for other Indonesian FMCG firms pursuing integrated HR strategy design.